IN VITRO STUDY OF PHYLLOSPHERE BACTERIA AS PROMISING BIOCONTROL AGENTS AGAINST BACTERIAL LEAF BLIGHT DISEASE (Xanthomonas oryzae pv. oryzae) IN RICE PLANTS - Masnilah, Rachmi; Nurmala, Fenny; Pradana, Ankardiansyah Pandu (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
This study aimed to explore the potential of phyllosphere bacterial isolates as biological control agents against Xanthomonas oryzae pv. oryzae (Xoo). We isolated a strain exhibiting typical morphological and biochemical characteristics of Xoo, such as a yellowish, spherical colony, Gram-negative, and starch hydrolyzing ability. This isolate was shown to cause necrotic lesions on rice leaves, corroborating its pathogenic nature. Subsequently, we isolated ten diverse phyllosphere bacteria from rice plants. These isolates were characterized based on various morphological and biochemical attributes including colony shape, margin appearance, color, growth time, and the ability to fluoresce under UV light when cultivated on King's B medium. Crucially, none of these isolates induced a hypersensitive response in tobacco leaves, an initial indicator of their potential as safe biological control agents. In an antagonistic assay against Xoo, all the phyllosphere isolates demonstrated varying levels of inhibition, suggesting their potential role in biological control. Two isolates, PGM1 and PGM4, exhibited the highest antagonistic effects against Xoo. These findings provide preliminary evidence for the potential use of these phyllosphere isolates in managing bacterial leaf blight in rice, warranting further research to confirm their efficacy and safety under field conditions.